<htm>Baptonedys, novo gênero para Lonchopria bicellularis Ducke (Hymenoptera, Colletidae) - Moure, Jesús Santiago; Urban, Danúncia; Graf, Vinalto (Acta Biológica Paranaense, 1999)
<htm>Baptonedys, novo gênero para Lonchopria bicellularis Ducke (Hymenoptera, Colletidae)